STATUS GIZI BALITA DI KABUPATEN BOGOR PADA KRISIS EKONOMI - Dewi Permaesih; Yuniar Rosmalina; Reviana Christijani; Sri Martuti; Susilowati Herman (Persagi, 2000)
NUTRITIONAL STATUS OF UNDERFIVE YEARS CHILDREN DURING ECONOMIC CRISIS AT BOGOR DISTRICT.Background: The relationships between nutritional status, growth and development of vital organ have been published else where. The increasing of body weight and height can be used as indicators of good nutritional status of ctildren under five of age. The prevalence of severe malnutrition of children under five years lends to increase. Vitamin A deficiency and anemia were also still problems in Indonesia. The periodic information about nutritional status of children less than five years of age is important.Method: The assessment of nutritional status of under five children had been conducted in the area of 10 Puskesmas in Kabupaten Bogor. The selection of these areas based on the survey in 1992. Data collection was carried out twice in April 1999 and November 1999. The assessment included vitamin A status, anthropometry and hemoglobin level.Results: The result shows there was no case of xerophthalmia among the children. However, analysis shows that 7.3% children under five of age have serum vitamin A level below 10 ug/dl in April 1999 and 6.8 in November 1999.The prevalence of severe malnutrition based on weight for age tend to increase 3.1% (in 1992), 3.9% (in April 1999), and 4.4% (in November 1999). The prevalence of underweight significantly increased (p<0.05) from 11.4% to 24%. The prevalence of wasting also shows significantly increased both at 0-23 months and 24-60 months of age from 4.7% to 13.9% and 6.3 to 11.6% respectively. The prevalence of stunting not significantly increased. The prevalence of anemia increased from 41.7% in 1992 to 48.7% in April 1999 and 49.2% in November 1999. However, the increase was not significant statistically.Key Words: underfive years old, nutritional status, vitamin A status, anemia status.